Detection Of Accessory Splenic Tissue On Liver/Spleen Colloid Scan – Another Marvel Of Spect/Ct - Areeba Amin; Xain Tauqeer; Mairah Razi (Journal of the Pakistan Medical Association, 2025)
Accessory splenic tissue is common after surgical intervention relating to spleen. However, it can occur by birth and in cases of idiopathic thrombocytopenic purpura (ITP). In ITP, accessory spleen can recur after splenectomy. Imaging modalities like CT and ultrasound serve as convenient tools for diagnosis of hepatic and splenic pathologies; however, their role is limited. Hybrid nuclear imaging can solve the mystery as it gives anatomical and targetted functional information. 99mTc labelled liver/spleen colloid scan has vast applications from detecting focal nodular hyperplasia to splenic remnants. We describe the case of a patient where colloid scan localized of suspected accessory splenic tissue after repeated surgery. Keywords: Liver/-Spleen Colloid, Splenectomy, SPECT/CT, Pneumothorax